2003
DOI: 10.1016/s0045-6535(02)00843-3
|View full text |Cite
|
Sign up to set email alerts
|

Frozen mitochondria as rapid water quality bioassay

Abstract: A rapid and relatively low cost bioassay, usable in routine screening water test has been developed modifying the beef heart mitochondria test. In our experiments, mitochondria (FM22) were frozen at )22°C, instead of )80°C (FM80), and their applicability and sensitivity was verified. The oxygen consumption was measured by a Clark electrode that was interfaced to a PC to collect test analysis data. Blank tests were carried out to verify the oxygen consumption linear fitting. Toxicity tests were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Studies of the in vitro toxicity of this compound have been performed on fish cells [4] and the viability of the cells has been evaluated using the Alamar Blue dye. It has been demonstrated that, in many cases, the preferential target of the toxic compounds responsible for acute toxicity are mitochondria [5–8]. Therefore, in this study, we used the mitochondria (from rat liver) to study the molecular effects of SN, because the behavior and the molecular structure of mitochondria is similar in all living species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the in vitro toxicity of this compound have been performed on fish cells [4] and the viability of the cells has been evaluated using the Alamar Blue dye. It has been demonstrated that, in many cases, the preferential target of the toxic compounds responsible for acute toxicity are mitochondria [5–8]. Therefore, in this study, we used the mitochondria (from rat liver) to study the molecular effects of SN, because the behavior and the molecular structure of mitochondria is similar in all living species.…”
Section: Introductionmentioning
confidence: 99%
“…Concentration−response relationships for cytotoxicity and MMP disruption were considered for individual chemicals or samples to quantify concentrations causing a 10% effect. The inhibitory concentration for a 10% reduction in cell viability was determined as IC 10 , and the effect concentrations for a 10% reduction of the MMP was determined as EC 10 . In case of oxidative stress, the effect concentration leading to an induction ratio (IR) of 1.5 (EC IR1.5 ) was derived, as described by Escher et al 15 Automated data evaluation was performed using R software (version 4.1.3).…”
Section: Surface Water and Wwtp Effluent Extractsmentioning
confidence: 99%
“…9 Due to the high environmental relevance of mitochondrial toxicity, it would be desirable to monitor the level of mitochondrial toxicants in environmental mixtures and extracts from biota and blood in biomonitoring studies. There have been attempts to monitor water quality based on oxygen consumption rate as an endpoint for mitochondrial toxicity using isolated mitochondria from bovine heart 10 or HepG2 cells. 11 To date, the quantification of the oxygen consumption rate remains limited to low-throughput systems in the 24-well or 96-well plate format.…”
Section: Introductionmentioning
confidence: 99%